1993
DOI: 10.1177/095646249300400406
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection among STD Patients—Kigali, Rwanda, 1988 to 1991

Abstract: To follow the progression of HIV seropositivity among heterosexual adults at risk for HIV infection in the country of Rwanda prospectively, up to 100 patients with sexually transmitted diseases (STD) were tested each month from 1988 to 1991 at the health centre of Biryogo, which is located in a very crowded sector of the capital city, Kigali. Each patient had a blood sample tested anonymously for the presence of HIV antibodies. HIV seropositivity was defined as a reactive ELISA test combined to a reactive West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…But non-genocidal rape did not remain statistically significant in multivariate models perhaps due to lower statistical power as only 15% of the sample had experienced non-genocidal rape compared to 50% experiencing genocidal rape. Other studies have also reported that women living with HIV who have a history of non-genocidal sexual abuse are susceptible to risky behaviors including inconsistent condom use, transactional sex, multiple partnerships and sexually transmitted infections, which may have occurred during the abuse (3338). Although prior experience of repeated sexual abuse particularly during childhood is associated with greater sexual risk behaviors and transactional sex (34), the influence of sexual trauma during war and conflict on subsequent risky sexual activity and transactional sex has not been well described.…”
Section: Discussionmentioning
confidence: 99%
“…But non-genocidal rape did not remain statistically significant in multivariate models perhaps due to lower statistical power as only 15% of the sample had experienced non-genocidal rape compared to 50% experiencing genocidal rape. Other studies have also reported that women living with HIV who have a history of non-genocidal sexual abuse are susceptible to risky behaviors including inconsistent condom use, transactional sex, multiple partnerships and sexually transmitted infections, which may have occurred during the abuse (3338). Although prior experience of repeated sexual abuse particularly during childhood is associated with greater sexual risk behaviors and transactional sex (34), the influence of sexual trauma during war and conflict on subsequent risky sexual activity and transactional sex has not been well described.…”
Section: Discussionmentioning
confidence: 99%
“…The HIV-1 epidemic continues to spread in Africa,1 but some studies have reported unchanging HIV-1 prevalence among adult populations in different regions in Burundi, Rwanda, and Zaire 2 3 4 5 6. In some of the major towns of Uganda the prevalence of HIV-1 among women attending antenatal clinics included in the national sentinel surveillance programme has declined since 1992; for example, the reported rates from the two main hospitals in Kampala, the capital city, fell from 29% to 22% in one hospital and to 17% in the other 7…”
Section: Introductionmentioning
confidence: 99%